Growth and Properties of ZnO:Al on Textured Glass for Thin Film Solar Cells - Marta Lluscà; Aldrin Antony; Joan Bertomeu (International Journal of Photoenergy)
Aluminium induced texturing (AIT) method has been used to texture glass substrates in order to enhance the photon absorption in thin film solar cells. The resultant glass roughness has been analyzed by varying the AIT process parameters and it has been found that the deposition method of Al is a decisive factor in tuning the texture. Two types of textures, a soft (texture E) and a rough texture (texture S), were achieved from the thermally evaporated and sputtered Al layers through AIT process. Aluminium-doped zinc oxide (AZO) layers of different thickness were deposited over both textures and over smooth glass. Haze values above 30% were obtained for texture S + AZO and above 10% for texture E + AZO. The resultant morphologies were free from sharp edges or deep valleys and the transparency and the resistivity values were also good enough to be used as front contact for thin film solar cells. In order to demonstrate the light absorption enhancement in a solar cell device, 200 nm of a-Si:H followed by 300 nm of Ag were grown over the textured and smooth substrates with AZO, and an optical absorption enhancement of 35% for texture E and 53% for texture S was obtained in comparison to the smooth substrate.